(untitled) (Journal of Fatima Jinnah Medical University, 2023)
Background: Mucin 1 (MUC1) is overexpressed in almost 90% of CA breast cases and is usually associated with poor prognosis. On the other hand, HER2 is profoundly expressed in breast carcinoma and is also linked with increased disease recurrence, tumor invasion and poor prognosis. Thus, this study was designed to assess the expression of MUC1 and HER2 against the histological grades of breast carcinoma in our population. Materials and methods: It was a cross sectional analytical study conducted at Post Graduate Medical Institute/General Surgery Departments of Lahore General Hospital (LGH), Lahore. Duration of study was 12 month from 27-3-2018 to 30-3-2019. Total 60 newly diagnosed cases of CA breast were included in the study. Immunohistochemistry technique was used and MUC1 and HER2 markers were applied to check the probable association between the two markers and the histological grades of cancer. Results: A total of 60 cases were included in the study, out of which 96.7% (n=58) were invasive ductal carcinoma, while 3.3% (n=2) were Invasive lobular carcinoma. Among the total, 60% (n=36) were found positive for MUC1 (moderate/strong) and 40% (n=24) were found negative (negative/weak). Regarding HER2, 26.7% (n=16) were strong positive, 20% (n=12) were at the borderline/equivocal and 53.3% (n=32) were found negative for HER 2. Conclusion: Statistically significant association was found between MUC1 and HER2 against the histological grades of breast cancer patients (p <0.05).